2013
DOI: 10.1021/ja400301k
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Coverage Density of Br Ions on Pd{100} Facets and Its Role in Controlling the Shape of Pd Nanocrystals

Abstract: We report an approach based on a combination of inductively coupled plasma mass spectrometry and X-ray photoelectron spectroscopy for quantitative analysis of the role played by Br(-) ions in the synthesis of Pd nanocrystals. The Br(-) ions were found to adsorb onto Pd{100} facets selectively with a coverage density of ca. 0.8 ion per surface Pd atom. The chemisorbed Br(-) ions could be removed via desorption at an elevated temperature under reductive conditions. They could also be gradually released from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
185
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(204 citation statements)
references
References 35 publications
10
185
0
6
Order By: Relevance
“…In addition, the presence of Br − ions shifted the equilibrium to the right based on Equation (8) , further promoting the galvanic replacement. Owing to the selective adsorption of Br − ions on Pd{100} facets, [ 76,91 ] the PtBr 6 2− complex was expected to have a higher concentration in the vicinity of the {100} facets. As a result, Pd atoms on the {100} facets of a nanocube were preferentially oxidized and dissolved by reacting with PtBr 6 2− ( Figure 5 A), leading to the formation of Pd-Pt concave nanocubes ( Figure 5 , B-D) and eventually octapods (Figure 5 E).…”
Section: Progress Reportmentioning
confidence: 99%
“…In addition, the presence of Br − ions shifted the equilibrium to the right based on Equation (8) , further promoting the galvanic replacement. Owing to the selective adsorption of Br − ions on Pd{100} facets, [ 76,91 ] the PtBr 6 2− complex was expected to have a higher concentration in the vicinity of the {100} facets. As a result, Pd atoms on the {100} facets of a nanocube were preferentially oxidized and dissolved by reacting with PtBr 6 2− ( Figure 5 A), leading to the formation of Pd-Pt concave nanocubes ( Figure 5 , B-D) and eventually octapods (Figure 5 E).…”
Section: Progress Reportmentioning
confidence: 99%
“…To date, CAs have played an important role on shape‐controlled synthesis of NCs,137, 138, 139, 140, 141, 142 and there are many successful examples in preparing Cu 2 O NCs 7, 8, 75, 107, 122, 125, 143. We will introduce some classic synthetic routes of Cu 2 O NCs enclosed by low‐index facets.…”
Section: Basic Growth Strategies For Cu2o Polyhedramentioning
confidence: 99%
“…62 Removal of PVP from noble metal surfaces generally requires more forcing conditions. 63 Several studies have shown that charge transfer and the co-ordination mode of PVP molecules with noble metal nanoparticles to be size dependent.…”
Section: Oxidation and Interaction Of Pvp With Pd Nanocrystalsmentioning
confidence: 99%